2011
DOI: 10.1080/15459624.2011.601710
|View full text |Cite
|
Sign up to set email alerts
|

Review: Lead Exposure in Battery Manufacturing and Recycling in Developing Countries and Among Children in Nearby Communities

Abstract: The battery industry is the largest consumer of lead, using an estimated 80% of the global lead production. The industry is also rapidly expanding in emerging market countries. A review of published literature on exposures from lead-acid battery manufacturing and recycling plants in developing countries was conducted. The review included studies from 37 countries published from 1993 to 2010 and excluded facilities in developed countries, such as the United States and those in Western Europe, except for providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(65 citation statements)
references
References 109 publications
2
55
2
6
Order By: Relevance
“…[23,24]. Blood lead levels were so high in each of the three exposed groups (A, B and C) compared with control, (p<0.05), (f-test), where, there was significance increase (p< 0.05) between groups (ANOVA), this agrees with, (Gottesfeld P, Pokhrel AK) [25]. The data showed that, there was significant decrease (p<0.05) of hemoglobin concentratin and white blood cell's count in all test groups against control (table 3).…”
Section: Discussionsupporting
confidence: 81%
“…[23,24]. Blood lead levels were so high in each of the three exposed groups (A, B and C) compared with control, (p<0.05), (f-test), where, there was significance increase (p< 0.05) between groups (ANOVA), this agrees with, (Gottesfeld P, Pokhrel AK) [25]. The data showed that, there was significant decrease (p<0.05) of hemoglobin concentratin and white blood cell's count in all test groups against control (table 3).…”
Section: Discussionsupporting
confidence: 81%
“…[28] The BLLs and air lead levels were higher in developing nations, that given the absence of monitoring and regulation in some countries, Research may be the only viable option for improving working conditions and preventing environmental pollution. [29] So in our study was high significant difference in eating and washing hands before eating between cases and controls, that is agrees with findings of other study in Iran [30] , this may be due to eating in areas exposed to the city with its lead-contaminated areas or forgetting to wash your hands before eating. Although the knowledge that they need to know how to protection from lead poisoning, but a few of them go to regular health checkup and knowledge about effect of lead.…”
Section: Methodssupporting
confidence: 92%
“…Our fi ndings support many reports Ho et al (27) suggested that high BLL detected in their workers was related to extensive contact with lead and use of unwashed hands while eating. Gottesfeld et al (28) reported that BLL and air lead levels in battery workers were higher in developing nations, probably as a consequence of quick development in lead acid battery trade and recycling in these countries.…”
Section: Resultsmentioning
confidence: 99%